Assessment of a blood preservation protocol for use in ferrets before transfusion. (15th March 2014) - Pignon, C.; Donnelly, T. M.; Todeschini, C.; Deschamps, J. Y.; Roux, F. A.
Abstract : Blood transfusion has been described in ferrets as a treatment for oestrus‐associated anaemia and as a life‐saving therapy following trauma, iatrogenic (usually surgery‐induced) anaemia, autoimmune haemolytic anaemia and pure red cell aplasia. Although blood banking is a common method for storage of feline and canine blood it is not currently done with ferret blood. The aim of this study was to determine the shelf‐life of ferret blood using the anticoagulant citrate‐phosphate‐dextrose‐solution with adenine (CPDA). Two male ferrets were used as blood donors. From each ferret, 6 ml of blood was taken from the cranial vena cava and stored in 10 ml polyethylene terephthalate (PET) blood tubes containing 1 ml of CPDA solution. Blood was taken from each ferret once per month for five months. These 10 blood samples were stored in a laboratory refrigerator at 4°C for four weeks. Biochemical (glucose, pH, lactate, potassium, sodium) and haematological (haematocrit, light microscopic blood smear examination) analyses were performed on the stored blood at days 0, 7, 14, 21 and 28. Biochemical analyses revealed a progressive decrease from day seven in the stored blood pH, glucose and sodium, with a concomitant increase in lactate and potassium. These results are attributable to the ongoing metabolism and deterioration of the red blood cells (RBC) while in storage, and are more rapid than described for human or canine stored blood. Haematological analyses revealed a progressive elevation of the haematocrit due to the appearance of hypochromic red blood cells and echinocytes beginning at day 7. Haemolysis was observed in the microhaematocrit capillary tube sample by day 21, and microscopic clots were visible on the blood smear by day 28. The low blood pH and the appearance of many hypochromic RBCs and some echinocytes from day 7 in CPDA‐stored ferret blood, suggest stored ferret blood has a short shelf‐life when compared with stored human or canine blood. We recommend that ferret blood stored in CPDA should not be used for transfusion after seven days of storage at 4°C.